What Role Did Management Practices Play in SME Growth Post-Recession? - Alex Bryson; John Forth (Institute for the Study of Labor (IZA), 2016)
Small and medium-sized enterprises (SMEs) are known to contribute significantly to aggregate economic growth. However, little is known about the role played by management practices in SME growth since recession. We contribute to the literature on SME growth by analysing longitudinal administrative data on firms' employment and turnover, taken from the UK's Business Structure Database (BSD), with data on management practices collected in face-to-face interviews from the HR Managers and employees who were surveyed as part of the 2011 British Workplace Employment Relations Survey (WERS). We find off-the-job training is the only management practice that is robustly and significantly associated with higher employment growth, increased turnover, and a decline in closure probabilities, over the period 2011-2014. The findings suggest SME investment in off-the-job training is sub-optimal in Britain such that firms could benefit economically from increasing the amount of off-the-job training they offer to their non-managerial employees.
Keywords: L25; M12; M50; M53; 330; SMEs; small and medium-sized enterprises; employment growth; sales; workplace closure; HRM; training; recession